ANALISIS KEMAMPUAN KOMUNIKASI SAINS SISWA PADA PEMBELAJARAN BIOLOGI KELAS X - Rianti Adisti Puspa Dewi; Budhi Akbar; Meitiani Meitiani (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2022)
This study aim to determine the ability of this type of communication science process skills of students in learning biology. This study was conducted in 2014-2015 school year from May to August 2015 in SMAN 12 Bekasi. The population in this study were students of class X of SMAN 12 Bekasi 2014-2015 school year, and the sample is graders totaling X.1 40 students taken using simple random sampling technique. The method used is descriptive quantitative. The results showed that the science process skills mastered type of communication skills of students considered good, with a percentage of 66%. Controlled communication skills of students in explaining the results of the experiment the percentage of 75%. Communication skills in creating graphics, and preparation of the report have a percentage of 65% and 64%, while communications capabilities make diagrams have a percentage of 59%. Debriefing history experienced by students is the habit of practicing create charts, graphs and tables, assessment reference in making charts, graphs, and tables, methods and model featuring charts, graphs, and tables, and preparations of report that create charts, graphs, and tables.Keywords: communication skills, learningbiology, high school student